A generalization of interval-valued optimization problems and optimality conditions by using scalarization and subdifferentials - KARAMAN, Emrah (Kuwait Journal of Science, 2021)
In this work, interval-valued optimization problems are considered. Ordering cone is used in order to obtain a generalization of interval-valued optimization problems on real topological vector spaces. Some definitions and their properties are obtained for intervals, defined according to ordering cone. The Gerstewitz’s function is used to derive scalarization for interval-valued optimization problems. Also, two subdifferentials of interval-valued functions are given by using subgradients. Some important optimality conditions are introduced via subdifferentials. An example is given to demonstrate results.